Caracterização comportamental e avaliação da qualidade de leite em caprinos da raça saanen no semiárido nordestino - Paulo, Jória Leilane de Albuquerque (2014)
Goats are social animals which groups are organized from dominance hierarchies, established by agonistic behaviors. The quality and productivity of the goat s milk can be influenced by the dominance hierarchy. In this context, the objectives of our work were describe the social and food behavior of Saanen goats in a semi-extensive production system; characterize the social organization from the assessment of dominance hierarchies in two seasonal periods and correlate the physicochemical quality of the goats milk according hierarchical position. The experiment was conducted in the EMPARN s experimental station, located in the district of Cruzeta/RN. We utilized 17 multiparous goats of the Saanen race, with different age and weight. The observations were performed in precipitation and drought phases. The scan method recorded the trough permanence and agonistic interactions by method "all occurrences" in the pasture the alimentary behaviors of eat, ruminate on foot, ruminate lying, leisure on foot, leisure lying and walk, by the focal animal sampling method. The goats milk was submitted to analyzes of: density, protein, fat, lactose, CSS and total solids. The animals spend most of the time feeding themselves, and the activities that demand greater energy expenditure are done in the morning. The animals changed the hierarchical structure during the seasonal periods because of the withdrawal of some individuals of the group, having more aggressive behavior in the rainy season. The dominant animal the lowet production, the more CSS and the lesser fat, the goat in the middle of the hierarchy was the one that obtained the best production and quality. We conclude that the Saanen goats adapt to the environment and the conditions of the group to ensure better survival and its production is influenced by the internal dynamics of the group